An overview of centralised middleware components for sensor networks. (2016) - Onderwater, Martijn
Sensors are increasingly becoming part of our daily lives: lighting control, environmental monitoring, and keeping track of energy consumption all rely on sensors. Access to these sensors and their networks is, unfortunately, often provided via proprietary protocols and data formats. To overcome such issues, middleware components have been employed to provide a universal interface to the sensor networks, hiding vendor-specific details. Recently, much attention in literature is aimed at what we define as 'centralised' middleware components, which consider sensor networks that have no capacity to run middleware components on the sensor nodes. In this paper we introduce the term 'centralised' for these middleware components, and illustrate their relevance using a literature review of existing middleware components. After an overview of their general architectural setup, we describe and discuss four important centralised middleware components. Finally, we identify directions of further research that will impact centralised middleware components in the near future.